Effect of metallic and non-metallic fibre percentages and aspect ratios on the mechanical properties of mixed fiber self- compacting concrete - Kumar, S. Vijaya; Kumar, B. Dean; Swami, B.L.P. (Journal of Structural Engineering, 2024)
In the present experimentation, Fibrous Self-Compacting Concrete (FSCC) using mixed fibers (steel and glass, steel,and polypropylene) have been studied for its mechanical properties. It is attempted to know the effect of fiber percentageas well as the aspect ratios of steel fibers in various combinations. The aspect ratios of steel fibers tried were 20,30 and40. Total fiber percentages adopted were 0.2, 0.4,0.6 and 0.8. Glass and polypropylene fibers have constant aspectratios. By this, the smooth, uninterrupted flow of fibrous Self-Compacting Concrete (SCC) was obtained. The extent towhich these fibers improve the mechanical properties of SCC is studied. Mineral admixtures of flyash and CondensedSilica Fume (CSF) were employed at 20% and 10% respectively as replacement of Ordinary Portland Cement (OPC)for additional beneficial properties. This investigation brings out the influence of mixed fibers at different percentageswith different aspect ratios of steel fiber on the structural properties of SCC. The admission of fiber at a certainpercentage contributes towards more compressive strength. A combination of glass with steel fiber contributed bettertensile strength and flexural strength compared to polypropylene with steel fibers.